Evaluation of soybean cultivars for the ecotono region cerrado pantanal (Research, Society and Development, 2022)
Soy has great social importance and significantly affects the economy of Brazil and the world. As it is cultivated in different regions, it is important to develop cultivars that adapt to the different microclimates of each location. From this perspective, it is essential to assess how cultivars behave in a given region before deploying it as a crop. The objective of this work was to evaluate agronomic characters in different soybean cultivars implemented in the Cerrado Pantanal ecotone. The experiment was conducted in the 2019/2020 crop year in the Plant Science sector of the State University of Mato Grosso do Sul - Aquidauana University Unit (UEMS/UUA), in the city of Aquidauana-MS. The experimental design was randomized blocks, with twenty-three treatments and four replications, evaluating 23 cultivars. After collecting and tabulating the data, they were submitted to multivariate analysis: Principal components and cluster analysis. Cultivar C11 stood out with the variable AP, an indirect contributing factor in productivity as well as AIV, which stood out for cultivars C13, C16 and C17. Cultivar C7 reached the highest average for MCG.